PHYSIOLOGICAL STATUS, BLOOD PROFILE AND BODY COMPOSITION OF SHEEP FED WITH CA-SAPONIFIED LEMURU OIL COATED BY HERBS - Dewi Apri Astuti; Asep Sudarman (Buletin Peternakan, 2015)
This study was aimed to evaluate the physiological status, blood profiles and body composition of sheep fed with Ca-saponified lemuru oil coated by herbs. Twenty fat-tailed sheep (av. BW 23±1.2 kg) were used in this experiment by using Completely Randomized Design with five treatments ration and four replications of each. Sheep fed with concentrate containing 3% Ca-saponified lemuru oil and king grass (1:1) ad libitum. Treatments were control diet without herbs (R1); Ca-saponified lemuru oil coated by curcumae domestica (R2); coated by Zingiber officinale Rosc (R3); coated by Eugenia polyantha (R4) and coated by Pluchea indica Less (R5). Data of physiological parameters were measured three times a day, in the morning, at noon and afternoon. Blood samples were collected at the end of the experiment through jugular vein, together with zero sample for Urea Space measurement. The variables observed were physiological data (heart rate, respiration rate, and rectal temperature), blood profiles (erythrocyte, hemoglobin, packed cell volume (PCV), leucocytes) and body composition (water, protein and fat) measured using Urea Space technique. Results of the study showed that sheep fed with Ca-saponified lemuru oil coated by herbs was not significantly different on heart rate, respiration rate and rectal temperature among treatments. Meanwhile, total leucocytes, neutrophil cell, and lymphocytes significantly increased (P<0.05) by the treatment. Body composition percentage (water, protein and fat) were same in all treatments, except the total body fat and energy retained. In conclusion, supplementation of 3% Ca-saponified lemuru oil coated by Curcumae domestica, Zingiber officinale Rosc, Eugenia polyantha and Pluchea indica Less in fat-tailed sheep had no effect on physiological parameters, but improved the leucocyte and neutrophil cells. Total body fat and energy retained lower compared to control treatment.(Key words: Body composition, Ca-saponified, Herbs, Lemuru oil, Urea space)